Synthesis and analysis of cupper nanoparticles produced by laser - et. al., Mu'ataz S. Al Hassan, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Cupper nanoparticles are generated by using Nd:YAG laser nanosecond pulses using the liquid laser ablation technique. Nd:YAG of 6 and 10 nanoseconds pulse length with variable energy in the range are the two systems used (700-760 mJ ).The formation of cupper nanoparticles has been abolished using TEM with identical size distribution It has also been observed that when identical laser parameters are used, the average nanoparticles sizes of 80 and 120 nm for cupper are used.Furthermore, to approximate the temperature distributions for both cupper nanoparticles, the theoretical Mie-Gans model was used. Another factor that has been found is that the maximum temperature for gold nanoparticles is between (1000 K) and (1400 K), especially for the preparation of nanoparticles in the presence of 10 ns Nd:YAG.